On the Functions of the Figure of Narrative Metalepsis in the Narratives of “Old Writing” - Efimenko, Alexander (Slavica, 2026)
This article, based on the works of Russian writers of the “old school,” analyses the functions of the narrative figure of metalepsis. The article points out the differences between the types of metalepsis: rhetorical and ontological. It then provides an overview of the typology of metalepsis functions, which are divided into diegetic and exegetical. The former includes the functions of introducing the figure of analepsis and the figure of prolepsis into the narrative, as well as the function of transitioning from one diegetic line to another. A separate function of metalepsis is the exegetical function, which is common to both types of metalepsis.